Efektifitas Komunitas ‘Baca Bareng di UPI’ Terhadap Tingkat Antusiasme Membaca Pada Mahasiswa Universitas Pendidikan Indonesia - Maryam, Salwa Isheeqa Azzahra; Purnala, Ginar Rangla; Syihab, Ransi Adya (Nanggroe: Jurnal Pengabdian Cendikia, 2024)
This research reviews the role and effectiveness of the "Read Together at UPI" reading community in increasing reading interest and literacy among Indonesian University of Education (UPI) students. In the developing digital era, where interest in reading is often eroded by technological advances, the existence of a reading community is becoming increasingly important to strengthen literacy culture. Through a descriptive qualitative approach, this research evaluates participants' perceptions, responses and suggestions for the reading community. The results showed that the majority of participants responded positively to the community, with high levels of support and a significant increase in interest in reading. Although there were variations in participants' perceptions and experiences, participation in the activities was considered a rewarding and motivating experience. Apart from that, this research also discusses the potential of the 'Read Together at UPI' reading community in increasing student literacy, as well as providing suggestions for increasing its effectiveness and positive impact. Thus, this research provides valuable insight for the development of literacy programs in higher education environments, confirming the important role of reading communities in strengthening interest in reading and literacy in the digital era.